The Role of Melatonin on NLRP3 Inflammasome Activation in Diseases - Burak Ibrahim Arioz; Emre Tarakcioglu; Melis Olcum; Sermin Genc (Antioxidants, 2021)
NLRP3 inflammasome is a part of the innate immune system and responsible for the rapid identification and eradication of pathogenic microbes, metabolic stress products, reactive oxygen species, and other exogenous agents. NLRP3 inflammasome is overactivated in several neurodegenerative, cardiac, pulmonary, and metabolic diseases. Therefore, suppression of inflammasome activation is of utmost clinical importance. Melatonin is a ubiquitous hormone mainly produced in the pineal gland with circadian rhythm regulatory, antioxidant, and immunomodulatory functions. Melatonin is a natural product and safer than most chemicals to use for medicinal purposes. Many in vitro and in vivo studies have proved that melatonin alleviates NLRP3 inflammasome activity via various intracellular signaling pathways. In this review, the effect of melatonin on the NLRP3 inflammasome in the context of diseases will be discussed.